Strategi Komunikasi Publik dalam Implementasi Pelayanan Keimigrasian pada Kantor Imigrasi Kelas 1 TPI Jakarta Timur - Karina Kharisma Noviana (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
The Class 1 Immigration Office of East Jakarta plays a vital role in providing efficient immigration services, including passport and visa issuance, residence permits, and monitoring violations. These services are regulated by Law No. 6 of 2011 on Immigration, Government Regulation No. 31 of 2013, and internal policies. This study aims to analyze the communication strategy used by the office in implementing immigration services through a qualitative approach, collecting data via interviews, observations, documentation, and literature studies. The study identifies three main components of the communication strategy: Knowledge Core, Shared Expectations, and Participative Culture. Findings show that the office’s communication strategy focuses on transparency, technology utilization, community engagement, external collaboration, and employee training. These efforts have helped maintain strong public relations and a positive image, as evidenced by the Public Service Quality Perception Survey (SPKP) results.